2008
DOI: 10.1007/s00066-008-1951-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Distant Metastasis in Head Neck Cancer Patients: Implications for Induction Chemotherapy and Pre-treatment Staging?

Abstract: Background and Purpose: Intensity modulated radiation therapy (IMRT) combined treatment approaches, surgical and radiodiagnostic advances, respectively, lead to improved local-regional control in head neck cancer (HNC). With increasing local-regional control, distant metastases (DM) become more meaningful. In some trials without concomitant chemotherapy, induction chemotherapy (IC) resulted in an absolute reduction of DM by ~10-15%. In order to define a more efficient selection of patients at risk for DM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
(42 reference statements)
2
21
2
1
Order By: Relevance
“…These results are in agreement with data from Carvalho et al [4]. In addition, Studer et al [21] have also shown that a gross tumor volume > 70 ml in combination with locoregionally advanced stages (≥ T3 N1-3) are risk predictors for distant metastases (DM) in H&N cancer patients [18]. There is no doubt that the risk of capsular rupture of neck nodes is related to the higher N2b,c/3 categories of the TNM classification [7].…”
Section: Risk Of Distant Metastases (Dm) In Adjuvant Treatment Of Sccsupporting
confidence: 82%
“…These results are in agreement with data from Carvalho et al [4]. In addition, Studer et al [21] have also shown that a gross tumor volume > 70 ml in combination with locoregionally advanced stages (≥ T3 N1-3) are risk predictors for distant metastases (DM) in H&N cancer patients [18]. There is no doubt that the risk of capsular rupture of neck nodes is related to the higher N2b,c/3 categories of the TNM classification [7].…”
Section: Risk Of Distant Metastases (Dm) In Adjuvant Treatment Of Sccsupporting
confidence: 82%
“…The urinary clearance of exogenous substances, such as (51)Cr-EDTA and inulin, are accepted as gold standards for GFR assessment. However, because of costs and inconvenience, plasma creatinine, creatinine clearance (ECC), and creatinine-based estimation formulas are most commonly used to measure renal function [7,8,13,14,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…RT alone, which had been the standard treatment for patients with unresectable tumors for many years, resulted in survival rates of < 25% and 2-year locoregional control (LC) rates of < 20% [1,2,17,23]. Several approaches have been tried in order to improve the prognosis of these patients [6,11,21,24]. Treatment outcome may be improved by adding concurrent chemotherapy [1,2,8,10].…”
mentioning
confidence: 99%